Compact laser accelerators for X-ray phase-contrast imaging - Najmudin, Z; Kneip, S; Bloom, MS; Mangles, S; Chekhlov, O; Dangor, A; Dopp, A; Ertel, K; Hawkes, S; Holloway, J; Hooker, C; Jiang, J; et al. (2014)
Advances in X-ray imaging techniques have been driven by advances in novel X-ray sources. The latest fourth-generation X-ray sources can boast large photon fluxes at unprecedented brightness. However, the large size of these facilities means that these sources are not available for everyday applications. With advances in laser plasma acceleration, electron beams can now be generated at energies comparable to those used in light sources, but in university-sized laboratories. By making use of the strong transverse focusing of plasma accelerators, bright sources of betatron radiation have been produced. Here, we demonstrate phase-contrast imaging of a biological sample for the first time by radiation generated by GeV electron beams produced by a laser accelerator. The work was performed using a greater than 300TW laser, which allowed the energy of the synchrotron source to be extended to the 10100 keV range. © 2014 The Author(s) Published by the Royal Society. All rights reserved.